Babies by design : the ethics of genetic choice - Green, Ronald Michael (Yale University Press, 2007)
"A leader in the bioethlcs community, Ronald M. Green offers a scientifically and ethically informed view of human genetic self-modification and the possibilities it presents for a better future. Fears of a terrible Brave New World scenario or a new eugenics movement are overblown, he maintains, and in the more likely future, genetic modifications may improve parents' ability to enhance their children's lives and may even promote social justice." "The author outlines the new capabilities of genomic science, addresses urgent questions of safety that genetic interventions pose, and explores questions of parenting and justice. He also examines the religious implications of gene modification. Babies by design are assuredly in the future, Green concludes, and by making responsible choices as we enter that future, we can incorporate gene technology in a new age of human adventure."